Spaniards in the wider world: The role of education in the choice of destination country - Héctor Bellido; Miriam Marcén; Marina Morales (IZA Journal of Development and Migration, 2021)
This paper examines the relationship between the education level of Spanish emigrants and their destination country. Since Spanish emigrants were born under the same laws and institutions, the differences in their destination countries can be due to dissimilarities in their level of education. To explore this, we use census microdata, covering the period from 2000 to 2007, of 21 countries with Spanish emigrants. Results suggest that with low unemployment rates, English- and Spanish-speaking countries are the most likely to become the host countries for more educated individuals, regardless of their location.
Keywords: I20; F22; 330; education; migration; Spain